Shaping global business conduct: The 2011 update of the OECD Guidelines for Multinational Enterprises - Manfred Schekulin (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
On May 25, 2011, US Secretary of State Hillary Clinton joined ministers from members of the Organisation of Economic Co-operation and Development (OECD) and developing economies to celebrate the Organisation's 50th anniversary and agree on an update of the OECD Guidelines for Multinational Enterprises, the fifth revision since their adoption in 1976. This marked the culmination of an intense one-year negotiating process involving a large number of stakeholders, international organizations and emerging economies.
Keywords: 330